2013
DOI: 10.1017/s1047951113001182
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular strain and strain rates are decreased in children with normal fractional shortening after exposure to anthracycline chemotherapy

Abstract: Despite having a normal fractional shortening, children exposed to anthracyclines have subclinical derangement of their left ventricular deformation as measured by decreases in strain and strain rate in both the circumferential and longitudinal axis. In particular, there was a profound decrease in diastolic strain rate following anthracycline exposure compared with controls. Whether the decline of strain or strain rate can predict future risk of developing cardiomyopathy requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 35 publications
4
41
0
1
Order By: Relevance
“…Only a few studies have previously reported myocardial strain measured with two-dimensional speckle tracking echocardiography after ALL [23,26,27] and other cancer treatment in childhood, [28][29][30][31][32][33] and to date, there are only two previously published studies on VVI in childhood cancer survivors. [32,33] Park et al studied VVI of the left ventricle from the apical four-chamber view in 14 children ࣙ3 years after anthracycline treatment (90-342 mg/m 2 ). Consistent with our findings, they found no differences in longitudinal measures between the survivors and controls, but suggested attenuated strain rate and diastolic strain rate at septal segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have previously reported myocardial strain measured with two-dimensional speckle tracking echocardiography after ALL [23,26,27] and other cancer treatment in childhood, [28][29][30][31][32][33] and to date, there are only two previously published studies on VVI in childhood cancer survivors. [32,33] Park et al studied VVI of the left ventricle from the apical four-chamber view in 14 children ࣙ3 years after anthracycline treatment (90-342 mg/m 2 ). Consistent with our findings, they found no differences in longitudinal measures between the survivors and controls, but suggested attenuated strain rate and diastolic strain rate at septal segments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other speckle tracking echocardiography methods have shown attenuations in longitudinal and circumferential strains and strain rate both during ALL treatment [27] and in anthracycline-treated long-term survivors of childhood cancers. [23,28] Instead of selecting just one short-axis plane as in previous studies, [23,27,28,33] we analyzed circumferential measures at three levels. Despite the differences in treatment characteristics and length of follow-up, we consider that our findings on circumferential strain and strain rate are in line with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…While EF is an adequate gross marker of cardiac function, it may not be sensitive enough to detect early cardiac dysfunction [13][14][15]. Zito et al demonstrated that there is enough variability in EF measurements that it is not sensitive to detect a decrease in EF less than 10% [7].…”
Section: Echocardiographymentioning
confidence: 99%
“…La ecocardiografía con ST, según estudios realizados en pacientes bajo quimioterapia con drogas con potencial cardiotóxico, 39,40 pudo detectar alteraciones en la función miocárdica con un strain longitudinal disminuido mucho antes de que la fracción de eyección, acortamiento fraccional u otros índices ecocardiográficos de mala función sistólica sean detectables, además, parece ser que la cardiotoxicidad aumenta si se utilizan en el tratamiento más de un fármaco. La ecocardiografía con ST al permitir la pronta detección de la falla miocárdica en este grupo de pacientes, permitirá una mejor orientación en su tratamiento y el uso oportuno de medicamentos de cardioprotección.…”
Section: Figuraunclassified